HLA‐C*08:01:25, a novel HLA allele, which has arisen by a silent mutation in codon 271. (8th May 2019) - Zhou, Dan; Zou, Hong‐Yan
Abstract : HLA‐C*08:01:25 differs from HLA‐C*08:01:01 by a single‐nucleotide substitution in exon 4.